VD_FINDINFO Décision / 2014 / 1060 vom 1. September 2014 - VD Tribunal cantonal (2014)
CLASSEMENT DE LA PROCÉDURE, INDEMNITÉEN GÉNÉRAL | 319 CPP (CH), 393 al. 1 let. a CPP (CH), 429 al. 1 let. a CPP (CH)